0094 The impact of demand and cognitive load on stress and performance in 2nd year medical students: A simulation study. (2nd November 2015) - Russ, Stephanie; MacKenzie, Rhoda K; Morrison, Ian; Morse, Jerry; Johnston, Marie; Bell, Cheryl; Patey, Rona
Abstract : Background: Simulation-based healthcare education is stressful, particularly for novice learners. 1 Added increased medical urgency (demand) in a scenario and additional cognitive load may increase stress further and reduce performance. Aim: To assess the impact of demand and cognitive load (CL) on stress and performance for second year medical students conducting a 12-lead ECG and drug calculation in a simulated setting. Methods: A 2 × 2 independent samples design was employed, with 'demand' (high, low) and 'CL' (high, low) as independent variables. Second year medical students were asked to conduct and interpret an ECG for a simulated patient, and to subsequently conduct a drug calculation. 'Demand' and 'CL' were manipulated via an SBAR delivered pre-simulation (e.g. patient with and without current chest pain, alarms in room). Performance measures included accuracy of ECG interpretation and drug calculation, time spent doing ECG and drug calculation, and compliance with patient safety checks (ID, hand-washing). A full one to one debrief followed. Stress was measured objectively (via heart rate) and subjectively via the STAI 2 (completed pre-simulation, post-simulation and post-debrief). Self-efficacy was also measured via self-report at these 3 time-points. Results: Fifty second year medical students completed the scenario. There were no group differences in performance or stress measures. State anxiety was on average high pre and post-simulation but reduced significantly post-debrief. High trait anxiety was associated with more time spent doing the ECG and lower self-efficacy scores pre and post-simulation (but not post-debrief). Discussion/Conclusion: In this modest sample, demand and CL did not affect medical students' performance in a simulated scenario. Simulation is anxiety provoking for all medical students and this may mask the impact of experimental manipulations. An effective debrief helps to reduce anxiety and enhance self-efficacy, even for those with high trait anxiety. References: Willhaus J. Measures of physiological and psychological stress in novice health professions students during a simulated patient emergency. 2013. DPN dissertation. Washington State University, College of Nursing Marteau TM, Bekker H. Development of a six-item short-form of the state scale of the Spielberger State-Trait Aniety Inventory. Br J Clin Psychol 1992;31 : 301–306